URBAN CORRIDOR AS A PUBLIC SPACE CASE STUDY : CORRIDOR PANTAI LOSARI STREET, MAKASSAR CITY - Ersina, Sriany (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2018)
Abstrak_ An ideal public space should be a common ground, open and accessible for all including for people with disabilities. However in fact, along the beach Losari in Makassar City have inaccessible public space. Ideally, the various people who use and do interaction in the public space should be accommodated in the space. The Potential for conflict exist whenever and wherever people contact. Conflict is natural, normal and inevitable whenever people interact together. The disagreement and the difference on values conflict can be indicated by the unavoidable situation in human relationship. Therefore, defining the difference and strategy to manage the conflict in public space will be the focus of the paper. A Synergy, compromise, accommodative action and using a power are among others of the strategy to manage conflict to create a built environment towards an open and accessible public place. A Public space is the common ground where people carry out the functional and ritual activities that bind a community, whether in the normal routines of daily life or in periodic festivities [3] Urban Corridors that deals with mostly public space should serve the public at large, the plural society and the variety of human behavior.Keywords : Public Space; Conflict in Public Place; Urban Corridor.